Pengembangan Media Pembelajaran Berbasis Reels dan Story Instagram pada Materi Pokok Larutan Elektrolit dan Non Elektrolit di SMA Negeri 1 Wawotobi - Wadina, Wadina; Maysara, Maysara; Marhadi, Muh. Alim (FKIP University of Mataram, 2025)
A study has been conducted on the development of learning media based on reels and instagram stories on the main material of Electrolyte and Non-Electrolyte Solutions. The purpose of this study. 1). To determine the feasibility of the Instagram application as a learning media on the material of Electrolyte and Non-Electrolyte Solutions at SMA Negeri 1 Wawotobi. 2). To determine student responses to the Instagram application that has been developed as a learning media on the material of Electrolyte and Non-Electrolyte Solutions at SMA Negeri 1 Wawotobi. This type of research is Research & Development (R&D) using the ADDIE development model. The instruments used are assessment/validation sheets (materials and media), teacher responses and student responses. The research sample was 15 grade XI students. The results of this study indicate that: (1) Learning Media Based on Reels and Instagram Stories have gone through the expert validation test stage with an average overall score of 87.74% (2) The student response questionnaire received a positive response with a percentage of 82.77%. From the results of this study, it can be concluded that the Instagram application that has been developed as a learning media that has been developed has very good feasibility and high practicality so that it can be used as a support in chemistry learning activities on the material of Electrolyte and Non-Electrolyte Solutions.